Application of ChatGPT in Business Management and Strategic Decision Making - Ikhsan Amar Jusman; Abu Muna Almaududi Ausat; Agus Sumarna (Politeknik Ganesha Medan, 2023)
In the era of globalisation and the information technology revolution, businesses are faced with increasingly complex and dynamic challenges. Business managers and company executives are required to make the right and fast strategic decisions to maintain the company's competitive advantage in a rapidly changing market. Along with the development of AI and NLP, technology applications in business management have undergone significant developments. One of the latest promising innovations is the use of ChatGPT in the context of business management and strategic decision-making. This research aims to investigate the application of ChatGPT in the context of business management and strategic decision-making. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that the application of ChatGPT in business management and strategic decision-making offers great potential for improving the efficiency, productivity and quality of decision-making. With its ability to provide quick responses, in-depth data analysis and personalised interactions, ChatGPT can be a valuable intelligent assistant for enterprises. Key benefits of using ChatGPT in business management are improved customer service, business process automation, and more data-driven decision-making.